Three adult cases of orbital hidrocystoma presenting with blepharoptosis - Ferraz, Lucieni B. [UNESP]; Burroughs, John R.; Satto, Larissa H. [UNESP]; Natsuaki, Kryscia L. [UNESP]; Meneguin, Roberta L. F. S. [UNESP]; Marques, Mariangela E. A. [UNESP]; Schellini, Silvana A. [UNESP] (Journal Of Clinical Medicine, 2015)
To report adult cases of superior orbital apocrine hidrocystoma. Retrospective case series of three patients with superior orbital apocrine hidrocystoma and blepharoptosis with review of the clinical aspects of each of the cases. All three cases presented with blepharoptosis. Two of the cases had occult hidrocystoma, and one was visibly subcutaneous at presentation. Although rare and more common along the eyelid margin, apocrine hidrocystomas may occur in the orbit leading to secondary blepharoptosis and should be included within the differential diagnosis of orbital cysts. Physicians should therefore be aware of this possibility.
Keywords: Apocrine; Blepharoptosis; Cyst; Eccrine; Hidrocystoma; Orbit; Orbital